Experimental test of the relation between coherence and path information. Issue 1 (December 2018) - Gao, Jun; Jiao, Zhi-Qiang; Hu, Cheng-Qiu; Qiao, Lu-Feng; Ren, Ruo-Jing; Tang, Hao; Ma, Zhi-Hao; Fei, Shao-Ming; Vedral, Vlatko; Jin, Xian-Min
Abstract Quantum coherence stemming from the superposition behaviour of a particle beyond the classical realm, serves as one of the most fundamental features in quantum mechanics. The wave-particle duality phenomenon, which shares the same origin, has a strong relationship with quantum coherence. Recently, an elegant relation between quantum coherence and path information has been theoretically derived. Here, we experimentally test such new duality byl 1 -norm measure and the minimum-error state discrimination. We prepare three classes of two-photon states encoded in polarisation degree of freedom, with one photon serving as the target and the other photon as the detector. We observe that wave-particle-like complementarity and Bagan's equality, defined by the duality relation between coherence and path information, is well satisfied. Our results may shed new light on the original nature of wave-particle duality and on the applications of quantum coherence as a fundamental resource in quantum technologies. Quantum coherence represents one of the most fundamental features in quantum mechanics and is closely linked to the concept of wave-particle duality. The authors report an experimental realisation which proves the relation between coherence and path information as recently derived theoretically.